Microplastics ingestion by marine fauna with a particular focus on commercial species: a systematic review - Marmara, Dimitra; Katsanevakis, Stelios; Brundo, Maria-Violetta; Tiralongo, Francesco; Ignoto, Sara; Krasakopoulou, Evangelia (Frontiers in Marine Science, 2023)
Over the past few decades, the scientific community has extensively investigated microplastics (MPs) and their interactions with marine organisms. In this study, we present a systematic review conducted to gather information on ingested MPs characteristics and involved organisms.Additionally, through meta-analysis, we aim to estimate MPs ingestion quantities in commercial marine species. A total of at least 822 marine species were reported to have ingested MPs for the period of 1972 to 2021. with Pisces (class: Teleostei) being was the most frequently examined group including 513 species reported to have ingested at least one MP and exhibited the widest range of mean MPs ingestion quantities (0.07-16.33 MPs/ind GIT), when among the different families. The studies that analyzed soft tissue focused on Gastropoda, Bivalvia, and Malacostraca (8.85, 3.64, 1.03 MPs/ind.) and Echinodermata (1.56 MP/g). Notably, there was high heterogeneity among and within most families. In total, MPs' most frequently found characteristics were fibers, measuring less than 1 mm, black in color, and composed of polyethylene (PE). The extensive range of descriptions highlights the importance of adopting harmonized methodological protocols to effectively address the MPs issue.